2021
DOI: 10.1159/000513283
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Severe Obesity during the COVID-19 Pandemic: How to Maintain an Adequate Multidisciplinary Nutritional Rehabilitation Program?

Abstract: Background: The COVID-19 pandemic is spreading all over the world, particularly in developed countries where obesity is also widespread. There is a high frequency of increased BMI in patients admitted to intensive care for SARS-CoV-2 infection with a major severity in patients with an excess of visceral adiposity. Patients at risk of severe SARS-CoV-2 acute respiratory syndrome are characterised by the high prevalence of pre-existing diseases (high blood pressure and cardiovascular disease, diabetes, chronic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
0
11
0
2
Order By: Relevance
“…Many of the studies have shown that obesity and its complications worsen COVID-19, increase the risk of severe complications, and even mortality. That is associated with increased intra-abdominal fat, endocrine and metabolic dysfunction, and systemic inflammation in the course of obesity [ 18 , 20 , 30 ]. Only 35% of our patients were aware of this risk.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the studies have shown that obesity and its complications worsen COVID-19, increase the risk of severe complications, and even mortality. That is associated with increased intra-abdominal fat, endocrine and metabolic dysfunction, and systemic inflammation in the course of obesity [ 18 , 20 , 30 ]. Only 35% of our patients were aware of this risk.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, the incorporation of new technologies among clinical treatments for obesity has increased steadily in the past few years and has taken on a special relevance during the COVID-19 crisis management. 14 For instance, eHealth interventions have shown promising long-term effects in the improvement of healthy lifestyle among PLWO. 15 Furthermore, virtual reality (VR) has been used in the treatment of eating disorders (EDs) and obesity and has been associated with a reduction in food cravings, improvement in body image and enhancement of emotion regulation skills.…”
Section: Open Accessmentioning
confidence: 99%
“…Some studies have claimed that telemedicine gives high levels of satisfaction in weight management centers and both patients and providers wish to see these visit types offered in the future [9,10]. Other authors have expressed the urgency for adequate hospitals' equipment for the diffusion of telemedicine to maintain a multidisciplinary relationship with patients [11]. Even before the pandemic, videoconferencing technologies had been proposed as a tool to maintain contact with patients living in rural areas [12].…”
Section: Dear Editormentioning
confidence: 99%